Nanoparticles with polymer molecular brushes grafted on surfaces as well as preparation method and application of nanoparticles

The nanoparticles are modified by polyhydroxy compounds to bring out the active site of halogenated compounds, and the ATRP reaction is carried out to prepare nanoparticles with surface grafted polymer molecular brushes, which solves the problem of the coordination complexation between polyhydroxy compounds and nanoparticles. The problem has achieved efficient application of nanoparticles in the fields of optics, drug carriers, nanomedicine, etc.

CN119143950APending Publication Date: 2024-12-17WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411327046.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The prior art has failed to effectively utilize the coordination complexation or adsorption between polyhydroxy compounds and nanoparticles, limiting its application potential in the fields of optical devices, drug carriers, nanomedicine, biosensing, etc.

Method used

The nanoparticles modified as primer anchors by polyhydroxy compounds, bring out the active sites of halogenated compounds, and carry out atom transfer radical polymerization (ATRP) reaction to prepare nanoparticles with surface grafted polymer molecular brushes to expand their application range.

Benefits of technology

The good dispersion and unique optical properties of nanoparticles in different solvents have been achieved, and the application potential of nanoparticles in the fields of optical devices, drug carriers, nanomedicine, biosensing, biological probes and other fields has been expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143950A_ABST
    Figure CN119143950A_ABST
Patent Text Reader

Abstract

The invention discloses nanoparticles with surfaces grafted with polymer molecular brushes as well as a preparation method and application of the nanoparticles. The preparation method comprises the following three steps: (1) modifying polyhydroxy compounds on the surfaces of the nanoparticles through coordination complexation or adsorption; (2) reacting the nano particle surface modified polyhydroxy compound with a halogenated compound to generate a halogenated compound active site which can be used for atom transfer radical polymerization (ATRP) reaction; and (3) carrying out ATRP (Atom Transfer Radical Polymerization) reaction on the tail end of the active site of the halogenated compound and the monomer for forming the molecular brush to obtain the nano particle with the surface grafted with the polymer molecular brush. The nanoparticles with the surfaces grafted with the polymer molecular brushes, prepared on the basis of the method, have good dispersity and unique optical performance in different solvents due to different types of molecular brushes, and the application potential of the nanoparticles in the aspects of optical devices, optical elements, drug carriers, nano medicine, biological sensing and biological probes is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials, and in particular to nanoparticles with surface grafted polymer molecular brushes, and a preparation method and application thereof. Background Art

[0002] The dispersibility of nanoparticles is very important for optical properties. Most of the research on surface modification of nanoparticles is in aqueous solution, usually modifying the surface of nanoparticles with water-soluble polymers to make them have good water dispersibility (paper, Chem. Eur. J, 2007, 13, 7153-7161; paper, Langmuir, 2018, 34, 9532-9539). Furthermore, considering that practical applications need to operate in non-aqueous solvents, researchers use low-volatile solvents to form a solvation layer on the surface of nanoparticles to improve the long-term stability of the system (paper, J. Mater. Chem, 2008, 18, 5041-5045). As for the dispersibility of nanoparticles in non-polar solvents, Yin et al. proposed that organosilanes with long alkyl chains were used to modify nanoparticles to stabilize them in hydrophobic media, and successfully assembled superparamagnetic colloids into ordered structures with magnetically tunable photonic properties in non-polar solvents. (Paper, J. Am. Chem. Soc, 2009, 131(10), 3484-3486; Paper, Adv. Optical. Mater, 2022, 10, 2201188) Polymer molecular brushes are a type of nanoscale brush-like structure composed of polymer molecules. This structure is usually composed of polymer chains and can form a brush-like shape with a certain degree of rigidity and elasticity. Polymer brushes can introduce specific functional groups on the surface of nanoparticles through chemical modification, significantly improving the dispersibility of nanoparticles. At the same time, nanoparticles modified with polymer molecular brushes have expanded their application potential due to the different types of molecular brushes.

[0003] Since polyols contain a large number of hydroxyl groups, they can be replaced by a new functional group through nucleophilic substitution reactions or chemical cross-linking reactions to obtain a polymer star core based on a polyol structure. Then, polymer arms grow from the core through atom transfer radical polymerization (ATRP) to form functionalized molecular brushes with polyols as primer anchors.

[0004] However, in the related art, the coordination, complexation or adsorption effect between polyhydroxy compounds and nanoparticles is not brought into play, which limits its application. Therefore, it is necessary to provide a simple method to use nanoparticles modified with polyhydroxy compounds as initiating anchors to bring out the active sites of halogenated compounds for ATRP reaction, to achieve the grafting of polymer molecular brushes on the surface of nanoparticles, and to expand the application potential of nanoparticles in optical devices, optical elements, drug carriers, nanomedicine, biosensors, and bioprobes. Summary of the invention In view of this, the present application provides a nanoparticle with a surface grafted polymer molecular brush and a preparation method and application thereof, the core of which is to provide a nanoparticle with a surface grafted polymer molecular brush using a polyhydroxy compound as a primer anchor.

[0005] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a nanoparticle with a surface grafted polymer molecular brush, comprising a core nanoparticle, a polyhydroxy compound and a polymer molecular brush. The core nanoparticle is modified with a polyhydroxy compound on its surface by coordination, complexation or adsorption, and the polyhydroxy compound is connected to the polymer molecular brush by a covalent bond.

[0006] Preferably, the particle size of the core nanoparticles is 1-300 nm. In a second aspect, the present application provides a method for preparing nanoparticles having a surface grafted polymer molecular brush, comprising the following steps: S1. using a solution containing a polyhydroxy compound to perform one or more coordination, complexation or adsorption on the core nanoparticles, washing away the free polyhydroxy compound in the system after the reaction, separating and retaining the solid product, and obtaining nanoparticles with surface coordination, complexation or adsorption of polyhydroxy compounds; S2. dispersing the nanoparticles with surface coordination, complexation or adsorption of polyhydroxy compounds in a solution containing a halogenated compound to react, and preparing nanoparticles with halogenated compound active sites that can be used for atom transfer radical polymerization (ATRP) reaction; S3. Under an inert atmosphere, the nanoparticles with halogenated compound active sites are placed in a prepolymer solution containing monomer molecules, catalysts and metal-modified ligands, so that the ends of the halogenated compound active sites react with the monomers that will form the molecular brushes through ATRP to obtain the nanoparticles with the surface grafted polymer molecular brushes.

[0007] Preferably, in step S1, the range of the core nanoparticles selected includes one or more of the oxides or sulfides of iron, copper, molybdenum, vanadium, manganese, cobalt, chromium, ruthenium, nickel, terbium, rhodium, tungsten, cerium, titanium, aluminum, zinc, cadmium, europium, gadolinium, and zirconium elements on the surface or in the core, and SiO2 nanoparticles; the polyhydroxy compound includes at least one of tannic acid, tea polyphenols, catechins, catechin lactones, flavonoids, anthocyanins, pyrogallol, gluconic acid, glucose, and gluconate.

[0008] Preferably, the polyhydroxy compound is a polyphenol hydroxy compound, including at least one of tannic acid, tea polyphenols, catechins, catechin lactones, flavonoids, anthocyanins, and pyrogallol.

[0009] Preferably, in step S2, the halogenated compound includes at least one of halogenated acyl bromide / acyl chloride / acyl iodide / acyl fluoride compounds, halogenated alkanes, halogenated esters, halogenated alkanoic acids and their derivatives, halogenated phenols, halogenated alcohols, halogenated epoxides, and halogenated polyethylene glycol azide compounds.

[0010] Preferably, in step S2, the halogenated compound is a brominated compound.

[0011] Preferably, in step S2, the reaction between the nanoparticles modified with polyhydroxy compounds and the halogenated compounds includes a nucleophilic substitution method and a chemical crosslinking method. The nucleophilic substitution method comprises the following steps: adding at least one of halogenated acyl bromide / acyl chloride / acyl iodide / acyl fluoride compounds, halogenated alkanes, and halogenated esters to a reaction solvent containing nanoparticles modified with polyhydroxy compounds, and performing a nucleophilic substitution reaction to obtain nanoparticles with active sites of halogenated compounds. The chemical crosslinking method comprises the following steps: adding at least one of halogenated alkanoic acid and its derivatives, halogenated phenols, halogenated alcohols, halogenated epoxides, and halogenated polyethylene glycol azide compounds to a reaction solvent containing nanoparticles modified with polyhydroxy compounds, and performing a chemical crosslinking reaction to obtain nanoparticles with active sites of halogenated compounds.

[0012] Preferably, in step S3, the monomer molecules include one or more of acrylic monomers, acrylamide monomers, phosphorylcholine monomers, styrene monomers, and monomers containing active functional groups such as hydroxyl, amino, and epoxy groups. The acrylic monomers include at least one of acrylic acid, ethyl acrylate, hydroxyethyl acrylate, methyl methacrylate, butyl methacrylate, and other acrylic esters; the acrylamide monomers include at least one of acrylamide, N-isopropylacrylamide, and other acrylamide derivatives; the phosphorylcholine monomers include at least one of 2-methacryloylethylphosphorylcholine and its derivatives; The styrene monomer includes at least one of styrene, sodium styrene sulfonate, allyl styrene and other styrene derivatives; the monomer containing active functional groups such as hydroxyl, amino, epoxy, etc. includes at least one of N-methacryloxyethylamine and glycidyl methacrylate; the catalyst includes one or more of CuBr, CuCl, and CuI; the metal-modified ligand includes one or more of 4,4-dimethyl-2,2-bipyridine, 2,2-bipyridine, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, diethylenediamine, tributylamine, pentamethyldiethylenetriamine, and tetramethylurea.

[0013] Preferably, the atom transfer radical polymerization reaction temperature is 50-200° C., and preferably, the reaction time is 1-6 h.

[0014] Preferably, step S3 further comprises adding a buffer solution.

[0015] Preferably, in step S3, the buffer comprises at least one of phosphate buffer, glycine buffer, triethanolamine buffer and Tris buffer.

[0016] In a third aspect, the present application provides an application of nanoparticles with surface grafted polymer molecular brushes in optical devices, optical elements, drug carriers, nanomedicine, biosensors, and bioprobes.

[0017] The beneficial effects of the present application are as follows: The present invention utilizes the coordination, complexation or adsorption between polyhydroxy compounds and nanoparticles, as well as the nucleophilicity and universal adhesion of polyhydroxy compounds, to bring out active sites of halogenated compounds that can be used for atom transfer radical polymerization (ATRP) reactions through a one-step reaction. At the same time, the nanoparticles of surface-grafted polymer molecular brushes prepared based on this method show good dispersibility and unique optical properties in different solvents due to different types of molecular brushes, and expand the application potential of nanoparticles in optical devices, optical elements, drug carriers, nanomedicine, biosensors, and bioprobes. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1It is a schematic diagram of the structure of nanoparticles with surface grafted polymer molecular brushes; Figure 2 is the FT-IR spectra of the tannic acid (TA) modified nanoparticles (MNPs@TA) and the nanoparticles with brominated compound active sites (MNPs@TA-Br) prepared in Example 2; Figure 3 is a SEM image of nanoparticles of surface-grafted polymer molecular brushes prepared in Example 2; Figure 4 This is a hydrated particle size distribution diagram of the nanoparticles of the surface grafted polymer molecular brush prepared in Example 2 before reaction, after reaction for 2 hours, and after reaction for 6 hours; Figure 5 The nanoparticles with surface grafted polymer molecular brushes prepared in Example 2 were reacted for 2 hours, and the reflection spectrum was obtained under an external magnetic field with N,N-dimethylformamide (DMF) as the dispersion solvent. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0020] The present application provides a nanoparticle with a surface grafted polymer molecular brush, comprising a core nanoparticle, a polyhydroxy compound and a polymer molecular brush. The core nanoparticle is modified with a polyhydroxy compound on its surface by coordination, complexation or adsorption, and the polyhydroxy compound is connected to the polymer molecular brush by a covalent bond. In the molecular brush of the present application, the polyhydroxy compounds have the following functions: the hydroxyl groups of the polyhydroxy compounds undergo coordination, complexation or adsorption with the nanoparticles, and have been widely used in the surface modification and functionalization of nanoparticles, thereby improving the dispersibility and stability of the nanoparticles; the addition of polyhydroxy compounds can affect the morphology and structure of the nanoparticles, and affect the optical properties of the nanoparticles; the nanoparticles modified with polyhydroxy compounds act as initiating anchors, bringing out the active sites of the halogenated compounds for the ATRP reaction, and can serve as the starting point for the growth of the polymer chain, thereby realizing the grafting of polymer molecular brushes on the surface of the nanoparticles; the polyhydroxy compounds have good substrate adhesion, realize the functionalization of the nanoparticles, and expand the application scenarios of the molecular brushes.

[0021] In the present invention, the active site of the halogenated compound is preferably the active site of the brominated compound; although the halogen active site can also be selected from fluorine (F), chlorine (Cl), and iodine (I); chlorine gas may pollute the environment, and fluorine and iodine are more expensive than bromine. At the same time, bromine atoms have good activity and reactivity in molecules, and bromine atoms are also easier to introduce into organic molecules and have good adsorption properties on the surface of nanoparticles.

[0022] In the present invention, the particle size of the core nanoparticles is 1-300nm, which can cover the diffraction and reflection of ultraviolet light, visible light and infrared light. It is worth noting that in the present application, the size and density of the polymer molecular brush can be regulated by regulating the reactant ratio and reaction conditions, which directly affects the size and action distance of the steric resistance on the surface of the nanoparticles grafted with the polymer molecular brush, and thus affects the distance between the nanoparticles. According to the Bragg equation mλ=2ndsinθ, the diffraction wavelength λ is closely related to the spherical center distance d of adjacent particles. The steric resistance generated by the polymer molecular brush grafted on the surface of the nanoparticles is different, which will affect the spherical center distance d of adjacent particles, thereby affecting the position of the diffraction wavelength λ.

[0023] The present application provides a method for preparing nanoparticles with surface grafted polymer molecular brushes, comprising the following steps: S1. using a solution containing a polyhydroxy compound to perform one or more coordination, complexation or adsorption on the core nanoparticles, washing away the free polyhydroxy compound in the system after the reaction, separating and retaining the solid product, and obtaining nanoparticles with surface coordination, complexation or adsorption of polyhydroxy compounds; S2. dispersing the nanoparticles with surface coordination, complexation or adsorption of polyhydroxy compounds in a solution containing a halogenated compound to react, and preparing nanoparticles with halogenated compound active sites that can be used for atom transfer radical polymerization (ATRP) reaction; S3. Under an inert atmosphere, the nanoparticles with halogenated compound active sites are placed in a prepolymer solution containing monomer molecules, catalysts and metal-modified ligands, so that the ends of the halogenated compound active sites react with the monomers that will form the molecular brushes through ATRP to obtain the nanoparticles with the surface grafted polymer molecular brushes.

[0024] The present invention utilizes the coordination, complexation or adsorption between polyhydroxy compounds and nanoparticles, as well as the nucleophilicity and universal adhesion of polyhydroxy compounds, to bring out the active sites of halogenated compounds that can be used for atom transfer radical polymerization (ATRP) reaction through a one-step reaction. At the same time, the nanoparticles of surface-grafted polymer molecular brushes prepared based on this method show good dispersibility and unique optical properties in different solvents due to different types of molecular brushes, and expand the application potential of nanoparticles in optical devices, optical elements, drug carriers, nanomedicine, biosensors, and bioprobes.

[0025] The grafting of polymer molecular brushes on the surface of nanoparticles in the present application is based on atom transfer radical polymerization (ATRP), the core of which is the introduction of free radical initiators. The present invention focuses on the active sites of brominated compounds and utilizes the nucleophilicity and universal adhesion of polyhydroxy compounds to directly bring the active sites into the reaction system through a one-step reaction.

[0026] In step S1, the core nanoparticles include one or more oxides or sulfides of iron, copper, molybdenum, vanadium, manganese, cobalt, chromium, ruthenium, nickel, terbium, rhodium, tungsten, cerium, titanium, aluminum, zinc, cadmium, europium, gadolinium, and zirconium on the surface or in the core, and one or more SiO2 nanoparticles. The nanoparticles of the present application are spherical, and spherical nanoparticles usually lead to uniform distribution of plasmon effects on the surface of the nanoparticles, while prism-shaped or prism-shaped nanoparticles may lead to more complex plasmon coupling effects. In step S1, the polyhydroxy compound includes at least one of tannic acid, tea polyphenols, catechins, catechin lactones, flavonoids, anthocyanins, pyrogallol, gluconic acid, glucose, and gluconate. In step S2, there are two methods for preparing nanoparticles with halogenated compound active sites: one is a nucleophilic substitution method; the other is a chemical crosslinking method. The nucleophilic substitution method comprises the following steps: adding at least one of halogenated acyl bromide / acyl chloride / acyl iodide / acyl fluoride compounds, halogenated alkanes, and halogenated esters to a reaction solvent containing nanoparticles modified with polyhydroxy compounds, and performing a nucleophilic substitution reaction to obtain nanoparticles with halogenated compound active sites.

[0027] The mechanism of preparing nanoparticles with halogenated compound active sites by nucleophilic substitution is as follows: the polyhydroxy compounds modified on the surface of nanoparticles can completely functionalize the halogenated compounds through nucleophilic substitution reactions. Specifically, the hydroxyl groups in the polyhydroxy compounds attack the carbon atoms in the halogenated compounds, so that the hydroxyl groups in the polyhydroxy compounds are replaced by new functional groups, and nanoparticles with halogenated compound active sites are obtained for subsequent atom transfer radical polymerization (ATRP); wherein, the concentration of the halogenated compound is greater than or equal to 5 mg / ml, the nucleophilic substitution reaction temperature is 25-100°C, and the reaction time is 0.5-12h. Halogenated compounds are highly active reagents, and rapid dripping may cause the reaction temperature to rise, and may even induce a violent exothermic reaction, so slow dripping is required to control the reaction process; excessively long dripping time may cause the reactants to undergo side reactions or uneven reactions during the dripping period, affecting the purity and yield of the product.

[0028] The mechanism of preparing nanoparticles with halogenated compound active sites by chemical crosslinking is that the hydroxyl groups of the polyhydroxy compound undergo chemical crosslinking reaction with the organic functional groups in the halogenated compound, and nanoparticles with halogenated compound active sites are obtained through a one-step reaction. In the chemical cross-linking method, the halogenated compound includes at least one or more of halogenated alkanoic acid and its derivatives, halogenated phenols, halogenated alcohols, halogenated epoxides, and halogenated polyethylene glycol azide compounds; such compounds have halogen active sites and contain organic functional groups that can undergo chemical cross-linking with hydroxyl groups, and the functional groups include but are not limited to at least one of carboxyl groups, amine groups, amide bonds, thiols, boric acid, epoxy groups, hydroxyl groups, aldehyde groups, and azide groups.

[0029] The mass ratio of the surface-modified polyhydroxy compound nanoparticles to the halogenated compound is 1:(0.5-10). If too much halogenated compound is added, side reactions may occur, while too little halogenated compound can only be partially modified, affecting the next step of the experiment.

[0030] In the chemical cross-linking method, the reaction time can also be shortened by adding a catalyst, which includes but is not limited to one or more of an acid catalyst, a basic catalyst, and a metal oxide. Different catalysts vary according to the type of reaction. Michael / Schiff base reaction: base catalysts, such as triethylamine (TEA), tetramethylamine (TEA), Tris, etc. Epoxy ring-opening reaction: acid or base catalysts, such as sulfuric acid, sodium hydroxide (NaOH), etc. Reaction of hydroxyl and boric acid: metal catalysts, such as palladium (Pd), copper (Cu), etc.

[0031] When the nanoparticles with halogenated compound active sites are prepared by chemical crosslinking in the present application, they can also be washed and centrifuged with one or more solvents selected from ethanol, water, and N,N-dimethylformamide after the reaction is completed.

[0032] In both methods of step S2, the reaction solvent includes but is not limited to one or more of methanol, ethanol, ethylene glycol, acetonitrile, toluene, dimethyl sulfoxide, dimethyl methyl ether, and water. The concentration of the surface-modified polyhydroxy compound nanoparticles is greater than or equal to 5 mg / ml.

[0033] In step S3, the monomer molecules include one or more of acrylic acid monomers, acrylamide monomers, phosphorylcholine monomers, styrene monomers and monomers containing active functional groups such as hydroxyl, amino, epoxy, etc. The acrylic acid monomers include at least one of acrylic acid, ethyl acrylate, hydroxyethyl acrylate, methyl methacrylate, butyl methacrylate and other acrylic esters; the acrylamide monomers include at least one of acrylamide, N-isopropylacrylamide and other acrylamide derivatives; the phosphorylcholine monomers include at least one of 2-methacryloylethylphosphorylcholine and its derivatives; The styrene monomers include at least one of styrene, sodium styrene sulfonate, allyl styrene and other styrene derivatives; the monomers containing active functional groups such as hydroxyl, amino, epoxy, etc. include at least one of N-methacryloyloxyethylamine and glycidyl methacrylate; the catalyst includes one or more of CuBr, CuCl, and CuI; the metal-modified ligands include one or more of 4,4-dimethyl-2,2-bipyridine, 2,2-bipyridine, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, diethylenediamine, tributylamine, pentamethyldiethylenetriamine, and tetramethylurea. The mass ratio of nanoparticles with halogenated compound active sites, monomer molecules, catalysts, and metal-modified ligands is 1:2-20:0.05-2:0.15-6.

[0034] In step S3, the solvent of the prepolymer solution is one or more of acetone, anisole, tetrahydrofuran, dimethyl sulfoxide, toluene, chlorobenzene, N,N-dimethylformamide, N-methylpyrrolidone, isopropanol, methanol, ethanol, ethylene glycol, propylene glycol, acetonitrile, and water.

[0035] In step S3, the atom transfer radical polymerization reaction temperature is 50-200° C., and preferably, the reaction time is 1-6 hours.

[0036] In some embodiments, step S3 further includes adding a buffer to improve the efficiency of the polymerization reaction and the product yield; after step S3, it also includes precipitating with methanol, washing with ethanol and water multiple times by centrifugation, and drying in a vacuum.

[0037] The present solution is further described below through specific embodiments.

[0038] Example 1 A method for preparing nanoparticles with surface grafted polymer molecular brushes comprises the following steps: S1. Tannic acid (TA) modified nanoparticles: SiO2 and TA were added in a mass ratio of 5:1 to 20 ml of ethanol solvent, and ultrasonic adsorption was performed at room temperature of 20-25°C for 30 minutes. After the reaction, the reaction was washed and centrifuged with ethanol solvent to remove excess reactants to obtain TA modified SiO2 nanoparticles (SiO2@TA), wherein the particle size of the core nanoparticle SiO2 was 60 nm; S2. Use nucleophilic substitution method to obtain nanoparticles with brominated compound active sites: dissolve 400 mg of TA-modified SiO2 nanoparticles in 20 ml of N,N-dimethylformamide (DMF), stir the solution with a magnetic force, and cool it to 0°C in an ice bath, then add 400 ul of 2-bromoisobutyryl bromide to the reaction solution dropwise for more than 30 min, stir magnetically at room temperature for 4 h, wash with ethanol solvent and water after the reaction, and store in anisole for later use to obtain SiO2 nanoparticles with brominated compound active sites (SiO2@TA-Br), which serve as the star core of the ATRP reaction polymer; S3. Add 100 mg of nanoparticles with brominated compound active sites (SiO2@TA-Br), 1 g of acrylamide monomer, 60 mg of 2,2-bipyridine, and 20 mg of CuBr into a flask containing 10 ml of anisole solvent, deoxygenate the mixture at room temperature for 30 min, and stir it at 50°C in a nitrogen atmosphere for 4 h. After polymerization, purify the polymer with anisole, precipitate with methanol, wash with ethanol and water for 2 to 3 times respectively, and then vacuum dry at 30°C for 12 h to obtain SiO2 nanoparticles grafted with polyacrylamide.

[0039] Example 2 A method for preparing nanoparticles with surface grafted polymer molecular brushes, comprising the following steps: S1. tannic acid (TA) modified nanoparticles: adding 4:1 mass ratio of tannic acid to 20 ml ethanol solvent; Fe3O4 and TA were subjected to ultrasonic adsorption for 30 min at room temperature of 20-25°C. After the reaction, the reaction was washed and centrifuged with ethanol solvent to remove excess reactants, thereby obtaining TA-modified Fe3O4 nanoparticles (Fe3O4@TA), in which the particle size of the core nanoparticle Fe3O4 was 170 nm. S2. Use nucleophilic substitution method to obtain nanoparticles with brominated compound active sites: dissolve 100 mg of TA-modified superparamagnetic Fe3O4 nanoparticles in 10 ml of dimethyl sulfoxide (DMSO), stir the solution with magnetic force, and cool it to 0°C in an ice bath, then add 100 ul of 2-bromoisobutyryl bromide to the reaction solution, the addition time is more than 30 min, stir magnetically at room temperature for 2 h, wash with ethanol solvent and water after the reaction, and centrifuge, and store in tetrahydrofuran for later use, to obtain Fe3O4 nanoparticles with brominated compound active sites (Fe3O4@TA-Br), which are used as star cores of ATRP reaction polymers; S3. Add 50 mg of nanoparticles with brominated compound active sites (Fe3O4@TA-Br), 800 mg of methyl methacrylate monomer (MMA), 60 mg of 2,2-bipyridine, and 20 mg of CuBr into a flask containing 10 ml of tetrahydrofuran solvent. Deoxygenate the mixture at room temperature for 30 min and stir it at 80°C in a nitrogen atmosphere for 6 h. After polymerization, purify the polymer with tetrahydrofuran, precipitate with methanol, wash with ethanol and water for 2 to 3 times respectively, and dry it in vacuum at 30°C for 12 h to obtain superparamagnetic Fe3O4 nanoparticles grafted with polymethyl methacrylate (Fe3O4@TA-Br@PMMA).

[0040] Figure 2 FT-IR spectra of tannic acid-modified Fe3O4 nanoparticles (Fe3O4@TA) and Fe3O4 nanoparticles with brominated compound active sites (Fe3O4@TA-Br) prepared in Example 2. Compared with Fe3O4@TA, the aromatic peak in Fe3O4@TA-Br shifted (1430 cm −1 ), the ester group is extended (1799cm −1 ), the methyl protons near the bromine atom cause the C-Br peak (712cm −1 ), confirming the occurrence of nucleophilic acyl substitution reaction.

[0041] Figure 3 is a SEM image of nanoparticles of surface-grafted polymer molecular brushes prepared in Example 2; Figure 4 The nanoparticles of the surface grafted polymer molecular brush prepared in Example 2 are the hydrated particle size distribution diagrams of the nanoparticles before reaction, after reaction for 2 hours, and after reaction for 6 hours. The hydrated particle size of the nanoparticles of the surface grafted polymer molecular brush increases with the extension of polymerization time. The average effective hydrated particle size of the Fe3O4@TA nanoparticles before reaction is 181.78 nm, the average effective hydrated particle size of the nanoparticles of the grafted polymer molecular brush after reaction for 2 hours is 376.62 nm, and the average effective hydrated particle size of the nanoparticles of the grafted polymer molecular brush after reaction for 6 hours is 892.61 nm.

[0042] Figure 5 The nanoparticles of the surface grafted polymer molecular brush prepared in Example 2 react for 2 hours, and the reflection spectrum under an external magnetic field with DMF as the dispersion solvent shows that the prepared nanoparticles grafted with polymethyl methacrylate have the properties of magnetically responsive photonic crystals. This is because the superparamagnetic Fe3O4 nanoparticles can be assembled into a one-dimensional (1D) chain structure end to end along the direction of the magnetic field due to the dipole-dipole interaction under an external magnetic field. When the steric drag and dipole-dipole interaction generated by the polymer molecular brush grafted on the surface of the nanoparticles are balanced after 2 hours of reaction, the formed 1D chain structure has good periodicity and stability. The periodic structure is the constructed magnetically responsive photonic crystal (MRPCs), which has optical properties, can produce structural colors, and can measure reflection spectra. However, the nanoparticles after 6 hours of reaction, with DMF as the dispersion solvent, produce weak structural colors, and the reflection spectrum cannot be measured under an external magnetic field. This is because after 6 hours, the hydrated particle size of the nanoparticles increased by more than 3 times compared to the nanoparticles without grafted polymer molecular brushes. The molecular brushes on the surface of the nanoparticles that are too long will form entanglements, which is not conducive to the nanoparticles stretching in the solvent and affecting the generated spatial repulsion, so it is impossible to produce better structural color.

[0043] Example 3 A method for preparing nanoparticles with surface grafted polymer molecular brushes comprises the following steps: S1. Tea polyphenols modified nanoparticles: Add TiO2 in a mass ratio of 5:1 to 20 ml of ethylene glycol solvent. and tea polyphenols, and ultrasonically adsorbed for 30 minutes at room temperature of 20-25°C. After the reaction, the reaction was washed and centrifuged with ethanol solvent to remove excess reactants, thereby obtaining tea polyphenol-modified TiO2 nanoparticles, wherein the particle size of the core nanoparticle TiO2 was 120nm; S2. Add 500 mg of tea polyphenol-modified TiO2 nanoparticles into a flask containing 10 ml of ethylene glycol and stir evenly, then add 1 ml of 2-bromobenzenethiol into the flask, adjust the pH of the solution to 8.5 with Tris, stir at 60°C for 3 h, wash with ethanol solvent and DMF after the reaction, and centrifuge, store in anisole for later use, and obtain TiO2 nanoparticles with brominated compound active sites; S3. Add 500 mg of TiO2 nanoparticles with brominated compound active sites, 10 g of ethyl acrylate monomer, 100 mg of 2,2-bipyridine, and 30 mg of CuBr into a flask containing 50 ml of DMF and anisole mixed solvent. Deoxygenate the mixture at room temperature for 30 min, stir it at 70 ° C in a nitrogen atmosphere for 6 h, and after polymerization, purify the polymer with tetrahydrofuran, precipitate it with methanol, wash it with ethanol and water for 2 to 3 times, and dry it in vacuum at 30 ° C for 12 h to obtain TiO2 nanoparticles grafted with polyethyl acrylate.

[0044] Example 4 A method for preparing nanoparticles with surface grafted polymer molecular brushes, comprising the following steps: S1. Nanoparticles modified with tea polyphenols: adding CeO2 in a mass ratio of 3:1 to 20 ml of ethanol solvent; and tea polyphenols, and ultrasonically adsorbed for 30 minutes at room temperature of 20-25°C. After the reaction, the mixture was washed and centrifuged with ethanol solvent to remove excess reactants, and tea polyphenol-modified CeO2 nanoparticles were obtained, wherein the particle size of the core nanoparticle CeO2 was 100nm; S2. Add 1 ml of N, N-carbonyldiimidazole to a flask containing 10 ml of DMSO containing 400 mg of 2-bromoisobutyric acid, stir at room temperature for 2 hours, then add 100 mg of tea polyphenol-modified CeO2 nanoparticles to the mixture, and allow the reaction to continue at 80°C for 12 hours. After the reaction is completed, wash with ethanol solvent and water, centrifuge, and store in DMSO for later use to obtain CeO2 nanoparticles with brominated compound active sites; S3. Add 20mg CeO2 nanoparticles with brominated compound active sites, 50ul (55.25mg) sodium styrene sulfonate monomer, 60mg 2,2-bipyridine, and 20mg CuCl into a flask containing 10ml of a mixed solvent of isopropanol and deionized water. Deoxygenate the mixture at room temperature for 30 min and stir it for 6h in a nitrogen atmosphere at 80℃. After polymerization, precipitate with methanol, and wash with isoamyl alcohol and deionized water (1:1 mixed solvent) 2~3 times. After vacuum drying at 30℃ for 12h, CeO2 nanoparticles grafted with sodium polystyrene sulfonate (PSS) were obtained. Since PSS carries sulfonate ions (SO3 - ), the sulfonate ion has a negative charge and binds to the sodium ion (Na + ) form ionic bonds, making the entire nanoparticle charged and can be used for the assembly of electrically responsive photonic crystals.

[0045] In this embodiment, the construction of the electrically responsive photonic crystal is similar to that of the magnetically responsive photonic crystal. The CeO2 nanoparticles grafted with PSS can be dispersed in an electrically responsive system with water as the electrolyte due to the surface hydrophilicity and surface charge. Under the action of the electric field, the nanoparticles reach a state of equilibrium under the action of electrostatic force, electric field, gravity, dipole and resistance, and are arranged into a short-range ordered structure. This ordered structure is the constructed electrically responsive photonic crystal.

[0046] The assembly of electrically responsive photonic crystals depends on electrophoretic motion. Tea polyphenols contain a large amount of catechol and pyrogallol aromatic ring structures. A large amount of phenolic hydroxyl groups can graft more sodium polystyrene sulfonate, increase the charge of the grafted polymer molecular brush structure with nanoparticles as the core, and thus increase the migration distance of the electrophoretic motion of the nanoparticles. The reason is that according to the calculation formula of the electric field force F=qE (F is the electric field force, q is the charge of the particle, and E is the electric field strength), under the same voltage, the larger the q, the larger the F, and the easier it is to achieve the electrophoretic motion of the particles. It shows that the nanoparticles with high charge in this application can obtain a larger migration distance under the same voltage. Further, according to the Bragg equation mλ=2ndsinθ, m is the diffraction order, n is the effective refractive index of the medium; d is the distance between the centers of adjacent particles; θ is the observation angle; λ is the wavelength of the diffraction peak position, the range of variation of d becomes larger, and the macroscopic performance can be a wide range of structural color regulation. On the other hand, since nanoparticles with high charge are more likely to undergo electrophoretic motion, they will have a larger particle migration distance at low voltage, thus achieving low-voltage rapid response. Lower voltage can not only reduce energy consumption, but also avoid the occurrence of electrolysis reaction during electrophoresis (for example, the voltage is lower than the hydrolysis voltage of 1.23V).

[0047] The principle of this embodiment is applicable to all cases where the surface of nanoparticles modified with polyphenolic hydroxyl compounds is grafted with ionic polymer molecular brushes, and also illustrates the advantages of polyphenolic hydroxyl structures in increasing the charge on the particle surface, increasing the range of color changes of the electroresponsive photonic crystal structure, and achieving low voltage rapid response.

[0048] Example 5 A method for preparing nanoparticles with surface grafted polymer molecular brushes, comprising the following steps: S1. Anthocyanin modified nanoparticles: adding ZnS in a mass ratio of 2:1 to 10 ml of ethanol solvent; and anthocyanins, and ultrasonically adsorbed for 30 minutes at room temperature of 20-25°C. After the reaction, wash with ethanol solvent The mixture was centrifuged to remove excess reactants, and anthocyanin-modified ZnS nanoparticles were obtained, wherein the particle size of the core nanoparticle ZnS was 200 nm.

[0049] S1. Add 50 mg of anthocyanin-modified ZnS nanoparticles into a flask containing 5 ml of ethanol and stir evenly. Then add 100 mg of 2-bromoisobutyramide and 1 ml of hydrogen peroxide (H2O2) into the flask. Adjust the pH of the solution to 8.5 with Tris. Stir at room temperature for 1 hour. After the reaction is completed, wash and centrifuge with ethanol solvent to remove excess reactants. Store in anisole for later use to obtain ZnS nanoparticles with brominated compound active sites. S2. Add 20mg ZnS nanoparticles with brominated compound active sites, 100ul (90.2mg) styrene monomer, 240mg 2,2-bipyridine, and 30mg CuCl into a flask containing 20ml anisole mixed solvent. Deoxygenate the mixture at room temperature for 30 min and stir it for 10h in a nitrogen atmosphere at 130℃. After polymerization, purify the polymer with anisole, precipitate with methanol, wash with ethanol and water for 2-3 times respectively, and dry it in vacuum at 30℃ for 12h to obtain ZnS nanoparticles grafted with styrene (PS).

[0050] Comparative Example 1 A method for preparing nanoparticles with surface grafted polymer molecular brushes is carried out according to the method of embodiment 2, except that there are no nanoparticles in the polymer molecular brush structure. The results show that since the building blocks of the photonic crystal structure are nanoparticles, the molecular brush structure without nanoparticles does not have the conditions to assemble into a periodic structure under an external magnetic field and cannot produce optical properties.

[0051] Comparative Example 2 A method for preparing nanoparticles with surface grafted polymer molecular brushes is carried out according to the method of implementation 4, wherein tea polyphenols are replaced with a silane coupling agent with amino groups, and the active sites of halogenated compounds with carbonyl groups are chemically cross-linked with amino groups to bring them into the active sites of atom transfer radical polymerization (ATRP). The results show that the charge of the grafted polymer molecular brush structure with nanoparticles as the core is reduced. In the construction of the electric field responsive photonic crystal mechanism, it is not conducive to the occurrence of electrophoretic movement, and the control range of structural color is narrowed. At the same time, due to the decrease in the surface charge of the nanoparticles, compared with using tea polyphenols as a triggering anchor, a larger voltage (greater than 1.23V hydrolysis voltage) is required in the electric field response to achieve the same nanoparticle migration distance, which increases energy consumption and makes electrolysis reaction inevitable. Changes in the colloidal solution or electrode will reduce the stability and reversibility of the electrical response. At the same time, the coordination effect of tea polyphenols and nanoparticles can increase the stability of the particles. If tea polyphenols are not used as a primer anchor to bring out the active sites, the nanoparticles will be more likely to aggregate and precipitate.

[0052] The present invention makes use of the coordination, complexation or adsorption effect between polyhydroxy compounds and nanoparticles, as well as the nucleophilicity and general adhesion of polyhydroxy compounds, to bring out the active sites of halogenated compounds that can be used for atom transfer radical polymerization (ATRP) reactions through a one-step reaction. At the same time, the nanoparticles of surface-grafted polymer molecular brushes prepared based on this method show good dispersibility and unique optical properties in different solvents due to the different types of molecular brushes, and expand the application potential of nanoparticles in optical devices, optical elements, drug carriers, nanomedicine, biosensors, and biological probes. The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A nanoparticle with a surface grafted polymer molecular brush, characterized in that: The invention comprises core nanoparticles, polyhydroxy compounds and polymer molecular brushes; the core nanoparticles are modified with polyhydroxy compounds on their surfaces through coordination, complexation or adsorption, and the polyhydroxy compounds are connected with the polymer molecular brushes through covalent bonds.

2. The surface-grafted polymer brush nanoparticles according to claim 1, characterized in that: The particle size of the core nanoparticles is 1-300nm.

3. A method for preparing nanoparticles of surface-grafted polymer molecular brushes as claimed in claim 1, characterized in that: The following steps are involved: S1. The core nanoparticles are subjected to one or more coordination, complexation or adsorption using a solution containing a polyhydroxy compound, and after the reaction, the free polyhydroxy compound in the system is washed away, and the solid product is separated and retained to obtain surface coordinated, complexed or adsorbed nanoparticles with polyhydroxy compounds; S2. dispersing the nanoparticles with a surface coordination complex or adsorbed polyhydroxy compound in a solution containing a halogenated compound for reaction to prepare nanoparticles with halogenated compound active sites that can be used for atom transfer radical polymerization (ATRP) reaction; S3. Under an inert atmosphere, the nanoparticles with halogenated compound active sites are placed in a prepolymer solution containing monomer molecules, catalysts and metal-modified ligands, so that the ends of the halogenated compound active sites react with the monomers that will form the molecular brushes through ATRP to obtain the nanoparticles with the surface grafted polymer molecular brushes.

4. The preparation method according to claim 3, characterized in that: In step S1, the core nanoparticles include one or more of oxides or sulfides of iron, copper, molybdenum, vanadium, manganese, cobalt, chromium, ruthenium, nickel, terbium, rhodium, tungsten, cerium, titanium, aluminum, zinc, cadmium, europium, gadolinium, zirconium, and SiO2 nanoparticles; the polyhydroxy compound includes at least one of tannic acid, tea polyphenols, catechins, catechin lactones, flavonoids, anthocyanins, pyrogallol, gluconic acid, glucose, and gluconate.

5. The preparation method according to claim 3, characterized in that: In step S2, the halogenated compound includes at least one of halogenated acyl bromide / acyl chloride / acyl iodide / acyl fluoride compounds, halogenated alkanes, halogenated esters, halogenated alkanoic acids and their derivatives, halogenated phenols, halogenated alcohols, halogenated epoxides, and halogenated polyethylene glycol azide compounds.

6. The preparation method according to claim 3, characterized in that: In step S2, the monomer molecules include one or more of acrylic acid monomers, acrylamide monomers, phosphorylcholine monomers, styrene monomers and monomers containing active functional groups such as hydroxyl, amino, epoxy, etc. The acrylic acid monomers include at least one of acrylic acid, ethyl acrylate, hydroxyethyl acrylate, methyl methacrylate, butyl methacrylate and other acrylic esters; the acrylamide monomers include at least one of acrylamide, N-isopropylacrylamide and other acrylamide derivatives; the phosphorylcholine monomers include at least one of 2-methacryloylethylphosphorylcholine and its derivatives; The styrene monomer includes at least one of styrene, sodium styrene sulfonate, allyl styrene and other styrene derivatives; the monomer containing active functional groups such as hydroxyl, amino, epoxy, etc. includes at least one of N-methacryloxyethylamine and glycidyl methacrylate; the catalyst includes one or more of CuBr, CuCl, and CuI; the metal-modified ligand includes one or more of 4,4-dimethyl-2,2-bipyridine, 2,2-bipyridine, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, diethylenediamine, tributylamine, pentamethyldiethylenetriamine, and tetramethylurea.

7. The preparation method according to claim 3, characterized in that: The atom transfer radical polymerization reaction temperature is 50-200°C.

8. The preparation method according to claim 3, characterized in that: The step S3 further includes adding a buffer solution.

9. The buffer according to claim 8 comprises at least one of phosphate buffer, glycine buffer, triethanolamine buffer and Tris buffer.

10. Use of the nanoparticles of the surface-grafted polymer molecular brushes as claimed in claim 1 in optical devices, optical elements, drug carriers, nanomedicine, biosensors, and bioprobes.

Citation Information

Patent Citations

  • Method for grafting environment response macromolecule on nano silicon dioxde surface

    CN101139426A

  • Preparation method of titanium dioxide based composite photocatalyst with visible-light response function

    CN103861649A

  • Preparation method and application of monodisperse nanoparticles capable of assembling magnetic photonic crystals

    CN117550651A

  • Preparation method and application of responsive photonic crystal

    CN117608010A

  • Polymerization initiating group-attached inorganic oxide particle and method for manufacturing the same, as well as polymer-modified inorganic oxide particle obtained by using this inorganic oxide particle and method for manufacturing the same

    JP2010168468A

Cited By

  • Developing embolism microsphere with high elasticity and high drug loading rate and preparation method of developing embolism microsphere

    CN121015946A